A multi-stage almost ideal demand system: the case of beef demand in colombia (2013)
The main objective in this paper is to obtain reliable long-term and shorttermelasticities estimates of the beef demand in Colombia using quarterlydata since 1998 until 2007. However, complexity on the decision process ofconsumption should be taken into account, since expenditure on a particulargood is sequential. In the case of beef demand in Colombia, a Multi-Stageprocess is proposed based on an Almost Ideal Demand System (AIDS). Theeconometric novelty in this paper is to estimate simultaneously all the stagesby the Generalized Method of Moments to obtain a joint covariance matrixof parameter estimates in order to use the Delta Method for calculating thestandard deviation of the long-term elasticities estimates. Additionally, thisapproach allows us to get elasticity estimates in each stage, but also, totalelasticities which incorporate interaction between stages. On the other hand,the short-term dynamic is handled by a simultaneous estimation of the ErrorCorrection version of the model; therefore, Monte Carlo simulation exercisesare performed to analyse the impact on beef demand because of shocks atdifferent levels of the decision making process of consumers. The results indicatethat, although the total expenditure elasticity estimate of demand forbeef is 1.78 in the long-term and the expenditure elasticity estimate withinthe meat group is 1.07, the total short-term expenditure elasticity is merely0.03. The smaller short-term reaction of consumers is also evidenced on priceshocks; while the total own price elasticity of beef is -0.24 in the short-term,the total and within meat group long-term elasticities are